(3eNJUQ eNJUQ TQM aQGFV eMeO GdTQGfis - (3Ydj Hf eMeO Hf eMehO Hf Ydis; (3Ydj Hf eMeO Hf Ydj GdbQTj GdHSWj CHh GdMSf, GdTgjQ HGdbdUGOj,J (B891 (3g` s
(3ChdgG (B:s
(3jbhd YHjO Gddg JYGdi Ydi Hf eMeO aEfi deG cfJ GNJUQJ TQMi daQGFV GdTQGfi s
(3BNQgG (B:s
(3hdcd CNJ GKfGf hKdGKhf hdcd BNQ SJI YTQ gcPG s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B10 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B230s
Keywords: (3Yde GdaQGFVs